Axonal Damage in Pediatric Multiple Sclerosis - Kuntz, Nancy L. (Pediatr Neurol Briefs, 2015)
Investigators from Georg August University, Gottingen, Germany, analyzed axonal pathology in brain biopsy and autopsy samples from 19 children with early multiple sclerosis (MS).